Prenatal nicotine sex-dependently alters adolescent dopamine system development - Dwyer, Jennifer B. (Transl Psychiatry, 2019)
Despite persistent public health initiatives, many women continue to smoke during pregnancy. Since maternal smoking has been linked to persisting sex-dependent neurobehavioral deficits in offspring, some consider nicotine to be a safer alternative to tobacco during pregnancy, and the use of electronic nicotine delivery systems is on the rise. We presently show, however, that sustained exposure to low doses of nicotine during fetal development, approximating plasma levels seen clinically with the nicotine patch, produces substantial changes in developing corticostriatal dopamine systems in adolescence. Briefly, pregnant dams were implanted on gestational day 4 with an osmotic minipump that delivered either saline (GS) or nicotine (3 mg/kg/day) (GN) for two weeks. At birth, pups were cross-fostered with treatment naïve dams and were handled daily. Biochemical analyses, signaling assays, and behavioral responses to cocaine were assessed on postnatal day 32, representative of adolescence in the rodent. GN treatment had both sex-dependent and sex-independent effects on prefrontal dopamine systems, altering Catechol-O-methyl transferase (COMT)-dependent dopamine turnover in males and norepinephrine transporter (NET) binding expression in both sexes. GN enhanced cocaine-induced locomotor activity in females, concomitant with GN-induced reductions in striatal dopamine transporter (DAT) binding. GN enhanced ventral striatal D2-like receptor expression and G-protein coupling, while altering the roles of D2 and D3 receptors in cocaine-induced behaviors. These data show that low-dose prenatal nicotine treatment sex-dependently alters corticostriatal dopamine system development, which may underlie clinical deficits seen in adolescents exposed to tobacco or nicotine in utero.